A study on coupling of the grassland pattern and the flood process in Poyang Lake based on the island biogeography theory. Issue 8 (19th July 2022) - Luo, Shiqi; Chen, Wenbo; Xiong, Qiongbing; He, Lei
Abstract: As a typical type of landscape in Poyang Lake, the largest freshwater lake in China, grassland has been deeply disturbed by the flooding process. However, how the vegetation landscape diversity responds to the flooding process of Poyang Lake remains unclear. In this paper, we randomly selected 10 grasslands in the period of a normal water level from 2010 to 2019 to study the coupling relationship between the vegetation landscape diversity and flooding process, and established the related models based on the island biogeography theory. The results are as follows. (1) There is a positive correlation between the grassland vegetation landscape diversity and grassland area, the best fitting model is the logarithmic function. (2) Using the general dynamic model of island biogeography as a reference, the model of diversity–area–flooding established by using the area of grassland and duration as predictor variables has the highest goodness-of-fit. (3) If grassland was flooded for 120–130 days and the maximum depth of flooding is not more than 2.5 m every year, the vegetation landscape diversity in grasslands will be the highest. The findings have provided an extension to the study of the response of vegetation to flooding processes, and provide a certain theoretical basis for the protection and management of the Poyang Lake ecosystem. HIGHLIGHTS: The vegetation landscape diversity is positively correlated with the grassland area in Poyang Lake, China. The island biogeography theory can well explain the vegetation landscape diversity. Flooding duration affects the vegetation landscape diversity more than maximum depth. When the grassland is flooded for 120–130 days and the flooding depth does not exceed 2.5 m, the vegetation landscape diversity will be the highest. Graphical Abstract